International Trade Problems and India: A Case Study - Ramachandran, R (Journal of Commerce and Trade, 2011)
The liberalisation of international trade in services will put them at an even greater disadvantage in terms of their government’s sovereignty and of developing their domestic service industries. However, just as there are vastly different levels of development among Third World countries, especially in India there are also differing views on the costs and the magnitude of these costs of freeing-up the trade in services. For instance, India had led a number of developing countries in opposing the inclusion of discussions on the trade in services in the Uruguay Round. Broadly speaking, both developed and developing countries benefit from a liberalisation of trade in services in terms of efficiency and competitiveness. The industrial countries would accrue large trade benefits from more liberal trade in services, since services constitute a large portion of their total exports. The paper emphasises on modern international trade, began with the industrial revolution and the decline of mercantilism. As the industrialised nations, became richer due to their control over manufacturing commodities and trade, they began demanding and producing more sophisticated and expensive products. They found that the only feasible sources of the goods they wanted were from other countries, and were also the only countries rich enough to buy the new manufactured goods they were producing. Thus, India has had a major challenge in the changing composition of imports and exports when effects of independent India’s economic polices started becoming clear.